2016
DOI: 10.1177/0004563216629997
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in overweight and obese subjects and normal weight individuals matched for age and gender

Abstract: Background Obesity is associated with a state of systemic inflammation, mediated by adipose tissue-derived cytokines that may also have metabolic effects, including an effect on insulin resistance. The aim of this study was to compare the serum profile of pro- and anti-inflammatory cytokines in obese and non-obese subjects. Methods A total of 242 subjects who were either overweight or obese (body mass index [BMI] ≥ 25 kg/m) and non-obese subjects (body mass index <25 kg/m), were recruited in Mashhad in northea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Unlike previous studies where only 1–3 cytokines were analyzed, recently 2 groups had analyzed the sera of obese patients for 12–24 analytes ( Tisato et al, 2013 ; Azizian et al, 2016 ). Azizian et al reported significant difference for only CCL2 while Tisato et al observed an increase in CXCL10 and IL-6 and a decrease in PDGF-BB in the sera of patients with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies where only 1–3 cytokines were analyzed, recently 2 groups had analyzed the sera of obese patients for 12–24 analytes ( Tisato et al, 2013 ; Azizian et al, 2016 ). Azizian et al reported significant difference for only CCL2 while Tisato et al observed an increase in CXCL10 and IL-6 and a decrease in PDGF-BB in the sera of patients with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is linked to both local and systemic inflammation [2][3][4][5]. In obese subjects, there is an elevated release of proinflammatory cytokines into serum derived from either adipocytes, stromal vascular fraction cells, or immune cells in adipose tissue [3,5,6]. This elevated cytokine release in obese individuals is a reversible condition, since even mild weight loss can reduce serum cytokine levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…Vice versa, looking at the levels of IFNs in our obese and control arms, they overlap with those expressed into literature (43).…”
Section: Discussionmentioning
confidence: 70%